2021
DOI: 10.1002/aenm.202102766
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability of Tin Halide Perovskite Photovoltaics Using a Bathocuproine—Copper Top Electrode

Abstract: with a useful lifetime of decades. Tin perovskites also offer narrower bandgaps than their lead analogues, enabling a greater proportion of the solar spectrum to be harvested. [4] The Achilles' heel of tin perovskites for PV applications is their higher susceptibility to oxidation in air which stems from the tendency of Sn 2+ to convert to the more thermodynamically stable +4 oxidation state upon exposure to ambient air. [5] The intrinsic resistance of the device stack to air ingress dictates the degree of pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 49 publications
(68 reference statements)
1
30
0
Order By: Relevance
“…43 ). The only variation is the degradation of the Ag electrodes by the corrosive gas emanating from the decomposed perovskite, consistent with the results reported by Hatton et al 64 .…”
Section: Resultssupporting
confidence: 91%
“…43 ). The only variation is the degradation of the Ag electrodes by the corrosive gas emanating from the decomposed perovskite, consistent with the results reported by Hatton et al 64 .…”
Section: Resultssupporting
confidence: 91%
“…The stability of the champion control device is in close agreement with that reported previously for devices with the same structure, fabricated in the same way in the same laboratory, but using a different batch of chemicals. [ 6 ] For the champion device with a Bi layer, η peaks after 35 hours and then degrades to 70% of the peak value (t 70 ) only after a further 100 h testing. Remarkably, 100% of the peak η is retained for 16 h before the onset of degradation.…”
Section: Resultsmentioning
confidence: 99%
“… Crystal structure. The crystal structure plays a critical role in stabilizing tin perovskite, as it affects the defect formation energy and band alignment. ,,, Mixing different cations in the perovskite structure has been shown to decrease the crystal strain and increase the defect formation energy, leading to improved stability. ,, Recent studies have demonstrated that adding larger organic cations, such as guanidinium, , azetidinium, or imidazolium, to the perovskite precursor solution can enhance the stability and increase the defect formation energy. Introducing bulky organic cations with heteroatoms can also affect the crystal formation energy, leading to improved stability.…”
Section: Discussionmentioning
confidence: 99%